1980
DOI: 10.3109/09638288009163961
|View full text |Cite
|
Sign up to set email alerts
|

Study of sensation and muscle twitch responses to spinal cord stimulation

Abstract: Electrically induced sensation and muscle twitches were studied in a group of 43 patients in whom epidural electrodes were percutaneously placed for the evaluation of the effect of spinal cord stimulation on modification of their impaired motor control. Mean stimulus strength for sensory threshold was 5.25 +/- 2.75 mA and the tolerance level was at the stimulus strength of 10.8 +/- 4.4 mA. Muscle twitches with short latencies were recorded in limb and trunk muscles within the segments at the stimulating cathod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 1 publication
1
22
0
Order By: Relevance
“…7,38,39 Ventral root (motor) ®bres are not activated in SCS. 38 Model calculations predict that the stimulus amplitude to excite a ventral root ®bre exceeds the value of a DR ®bre of the same calibre 14 times (WA Wesselink, J Holsheimer, unpublished results).…”
Section: Conclusion From Scs Modellingmentioning
confidence: 99%
“…7,38,39 Ventral root (motor) ®bres are not activated in SCS. 38 Model calculations predict that the stimulus amplitude to excite a ventral root ®bre exceeds the value of a DR ®bre of the same calibre 14 times (WA Wesselink, J Holsheimer, unpublished results).…”
Section: Conclusion From Scs Modellingmentioning
confidence: 99%
“…Using fre quencies above 30 Hz, patients reported a feeling of vibration or 'buzz ing' in the segment adjacent to the epidurally placed cathode. The report ed sensation was variable between patients but quite constant for an indi vidual as long as the cathode did not move [5]. Through neurophysiolo- gical assessment of electrode position, we frequently found that although the electrodes were thought to be in an ideal position, as determined through fluoroscopy, they were not so well placed functionally.…”
Section: Physiological Observationsmentioning
confidence: 99%
“…The position of the electrode was veri®ed by¯uoroscopy (AP and lateral X-rays) and muscle twitch distribution patterns. 21 Muscle twitches during intraoperative testing were elicited using a train of 5 Hz at a pulse width of 210 ms, intensifying the amplitude in 0.5-V increments from 0 to 10 at two dierent polarities (37/0+ versus 07/3+). The de®nitive location of the electrode was determined based on muscle twitch responses by the quadriceps and adductor muscles elicited at an amplitude of 1 ± 4.5 V and a pulse width of 210 ms. For a detailed description of this procedure, the reader is referred to the ®rst paper of this series.…”
Section: Site Of Stimulationmentioning
confidence: 99%